Aralia taibaiensis Protects against I/R-Induced Brain Cell Injury through the Akt/SIRT1/FOXO3a Pathway. (12th May 2019) - Duan, Jialin; Cui, Jia; Zheng, Hongnan; Xi, Miaomiao; Guo, Chao; Weng, Yan; Yin, Ying; Wei, Guo; Cao, Jinyi; Wang, Yanhua; Wen, Aidong; Qiao, Boling
Abstract : Background . Saponin from Aralia taibaiensis (sAT) showed excellent antioxidative effects in several models; however, its effects on brain cells were unknown to us. The present study was designed to evaluate the protective effects of sAT on ischemia/reperfusion- (I/R-) induced injury and clarify its mechanisms. Methods . In vitro, HT22 cells were pretreated with sAT and then subjected to I/R. Apoptosis rate, mitochondrial function, and antioxidant proteins were measured. To clarify the mechanisms, siRNA were used. In vivo, sAT was pretreated through intragastric administration for 7 days and the I/R model was induced. The neurobehavioral scores, infarction volumes, and some cytokines in the brain were measured. Protein levels were investigated by Western blotting. Results . The results showed that sAT treatment significantly protected cells from I/R-induced cell apoptosis and mitochondrial dysfunction. The antioxidant protein levels were increased in a dose-dependent manner. Further study revealed that sAT induced the deacetylation and phosphorylation of PGC-1 α and FOXO3a. sAT treatment also induced the phosphorylation levels of Akt and the expression levels of SIRT1. Using the specific targeted siRNA transfection, the interplay relationship between Akt, SIRT1, PGC-1 α, and FOXO3a was verified. Furthermore, the same protective effects were also observed in rats subjected to I/R. Conclusion . sAT protected brain cells from I/R-induced mitochondrial oxidative stress and dysfunction through regulating the Akt/SIRT1/FOXO3a/PGC-1 α pathway.